2006
DOI: 10.1002/art.22339
|View full text |Cite
|
Sign up to set email alerts
|

Using internet technology to deliver a home‐based physical activity intervention for patients with rheumatoid arthritis: A randomized controlled trial

Abstract: Objective. To compare the effectiveness of 2 Internet-based physical activity interventions for patients with rheumatoid arthritis (RA). Methods. A total of 160 physically inactive patients with RA who had a computer with Internet access were randomly assigned to an Internet-based physical activity program with individual guidance, a bicycle ergometer, and group contacts (individualized training [IT] group; n ‫؍‬ 82) or to an Internet-based program providing only general information on exercises and physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
223
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(227 citation statements)
references
References 46 publications
4
223
0
Order By: Relevance
“…Similarly, Neuberger et al showed that patients taking part in a 12-week class exercise program experienced significant amelioration in disease-related parameters, whereas home-based exercise did not have that result, probably because patients in this group exercised at a lower intensity (29). Indeed, most of the studies reporting positive effects of exercises on quality of life were supervised intervention trials (3,20,24), whereas most of the studies in which this outcome was not modified were home-based exercises (25). It is likely that supervised exercises result in higher adherence to the exercise program and positive group enthusiasm, explaining the trend of higher SMDs in subsets of trials with supervised intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Neuberger et al showed that patients taking part in a 12-week class exercise program experienced significant amelioration in disease-related parameters, whereas home-based exercise did not have that result, probably because patients in this group exercised at a lower intensity (29). Indeed, most of the studies reporting positive effects of exercises on quality of life were supervised intervention trials (3,20,24), whereas most of the studies in which this outcome was not modified were home-based exercises (25). It is likely that supervised exercises result in higher adherence to the exercise program and positive group enthusiasm, explaining the trend of higher SMDs in subsets of trials with supervised intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 14 trials with cardiorespiratory aerobic exercise conditioning, the intervention fulfilled the dynamic exercise program criteria in 5 studies (5,8,20 -22). The control group underwent range of motion exercises in 3 studies (5,22,23), non-aerobic exercises in 1 study (24), education programs in 2 studies (3,25), and usual care in 8 studies (8,20,21,26 -30).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Lyngberg et al 43 Numerical values, estimates of variability and p values not given for outcome measures 28 Linking powered by eXtyles Marcora et al 44 Not randomised Minor et al 45 Mixed RA / osteoarthritis groups Minor, Hewett 46 Not randomised Moffet et al 47 Observational study (no control group) Nordemar 49 Nordemar et al 48 Not randomised Noreau et al 50 Not randomised Neuberger et al 51 Observational study (no control group) Stenstrom et al 52 Not randomised Stenstrom et al 53 Intervention compared is cognitive therapy Stenstrom et al 54 Study group with mixed types of inflammatory arthritis van den Berg et al 55 Internet study; primary outcome measure is physical activity 29 Linking powered by eXtyles…”
mentioning
confidence: 99%
“…So far, intervention studies of HEPA in RA have been evaluated in two randomized controlled studies with partially contradictory results. One study reported increased HEPA levels but no effects on health-related outcome [10], while the other found improvements in perceived health and muscle function without being able to demonstrate any change in HEPA levels [11]. Thus, the mechanisms behind the positive outcome were unclear and the providers´ coaching skills were not measured.…”
Section: Health-enhancing Physical Activitymentioning
confidence: 99%